2019
DOI: 10.3390/w11091786
|View full text |Cite
|
Sign up to set email alerts
|

Protecting a Pumping Pipeline System from Low Pressure Transients by Using Air Pockets: A Case Study

Abstract: This paper presents a case study of an existing water pipeline with five pumping stations each equipped with five pumps. In order to study the pipeline behavior prior to putting the system into operation, several transient simulations for different scenarios were developed. Results revealed that the most serious situation occurred when a simultaneous failure of the five pumps occur at each station caused by power cut, producing negative pressure waves because the system for control of hydraulic transients of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The determination of these points is, one lies on the system curve, the second on the efficiency curve, and the third one is the value of BHP that is computed from Eq. (10).…”
Section: Figure 2 Illustration Of Pump Performance and System Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of these points is, one lies on the system curve, the second on the efficiency curve, and the third one is the value of BHP that is computed from Eq. (10).…”
Section: Figure 2 Illustration Of Pump Performance and System Curvesmentioning
confidence: 99%
“…The study concluded that to understand the overall impact on the performance of a pumping system it is essential to study the feasibility of such measures that can optimize the data and improve the performance of the network based on a municipal water distribution system. Rafael et al [10] presented a study to examine the pipeline behavior before putting the system into operation. The case study is an existing water pipeline system consisting of five pumping stations each station is equipped with five pumps.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic transient situation within the pressurized system (Figure 2(a)) was first simulated and analyzed without an elevated tank and then by integrating an elevated tank at diverse locations in the system. In all simulations, the surge analysis was performed due to the sudden failure of all operating pumps during the peak hour, as it is the worst scenario as reported by Tullis (1989) and Carmona-Paredes et al (2019). The tank was modeled according to the continuity equation, and its site was identified arbitrarily; close to the pumping plants (J 1 and J 3 ), in the middle (J 13 and J 17 ), and at the boundary of the network (J 21 and J 22 ).…”
Section: Hydraulic Transient Simulationsmentioning
confidence: 99%